The Oxford Classification predictors of chronic kidney disease in pediatric patients with IgA nephropathy - Rafaela C.G. Fabiano; Stanley A. Araújo; Eduardo A. Bambirra; Eduardo A. Oliveira; Ana Cristina Simões e Silva; Sérgio V.B. Pinheiro (Elsevier, 2017)
Objective: The Oxford Classification for Immunoglobulin A nephropathy (IgAN) identifies pathological variables that may predict the decline of renal function. This study aimed to evaluate the Oxford Classification variables as predictors of renal dysfunction in a cohort of Brazilian children and adolescents with IgAN. Methods: A total of 54 patients with IgAN biopsied from 1982 to 2010 were assessed. Biopsies were re-evaluated and classified according to the Oxford Classification. Multivariate analysis of laboratory and pathological data was performed. The primary outcomes were decline of baseline estimated glomerular filtration rate (eGFR) greater than or equal to 50%. Results: Mean follow-up was 7.6 ± 5.0 years. Mean renal survival was 13.5 ± 0.8 years and probability of decline ≥50% in baseline eGFR was 8% at five years of follow-up and 15% at ten years. Ten children (18.5%) had a decline of baseline eGFR ≥ 50% and five (9.3%) evolved to end-stage renal disease. Kaplan-Meier analysis showed that baseline proteinuria, proteinuria during follow-up, endocapillary proliferation, and tubular atrophy/interstitial fibrosis were associated with the primary outcome. Multivariate Cox analysis showed that only baseline proteinuria (HR, 1.73; 95% CI, 1.20-2.50, p = 0.003) and endocapillary hypercellularity (HR, 37.18; 95% CI, 3.85-358.94, p = 0.002) were independent predictors of renal dysfunction. No other pathological variable was associated with eGFR decline in the multivariate analysis. Conclusion: This is the first cohort study that evaluated the predictive role of the Oxford Classification in pediatric patients with IgAN from South America. Endocapillary proliferation was the unique pathological feature that independently predicted renal outcome. Resumo: Objetivo: A Classificação Oxford para a Nefropatia por Imunoglobulina A (IgAN) identificou variáveis patológicas de risco para disfunção renal. O presente estudo teve como objetivo avaliar as variáveis da Classificação de Oxford como preditores de disfunção renal em crianças Brasileiras com IgAN. Métodos: Foram analisados 54 pacientes com diagnóstico de IgAN entre 1982-2010. As biópsias renais foram reavaliadas pela Classificação de Oxford. Foram realizadas análises uni e multivariada das variáveis clínicas e patológicas. O desfecho primário foi queda da taxa de filtração glomerular (TFG) ≥50% da filtração basal. Resultados: O acompanhamento médio foi 7,6 ± 5,0 anos. A sobrevida renal média foi 13,5 ± 0,8 anos e a probabilidade de atingir o desfecho primário foi 8% em 5 anos e 15% em 10 anos de seguimento. Dez crianças (18,5%) apresentaram queda na TFG basal ≥50% e 5 (9,3%) evoluiu para doença renal crônica terminal. A análise de Kaplan-Meier mostrou que a proteinúria basal e de seguimento, a proliferação endocapilar e a atrofia tubular/fibrose intersticial foram associadas com o desfecho primário. A análise multivariada de Cox mostrou que a proteinúria basal (HR = 1.73; IC95% 1.20-2.50, p = 0.003) e a proliferação endocapilar (HR = 37.18; IC95% 3.85-358.94, p = 0.002) foram preditores independentes de disfunção renal. Nenhuma outra variável patológica foi associada com declínio da TFG na análise multivariada. Conclusão: Este é o primeiro estudo brasileiro que avaliou a Classificação Oxford em crianças com IgAN. A proliferação endocapilar foi a única característica patológica capaz de predizer independentemente o declínio da função renal. Keywords: IgA nephropathy, Glomerulonephritis, Chronic kidney disease, Proteinuria, Oxford Classification, Palavras-chave: Nefropatia por IgA, Glomerulonefrite, Doença renal crônica, Proteinúria, Classificação de Oxford